THE CATHODIC CLEAVAGE OF THE NITROBENZENESULFONYL GROUP FROM ALIPHATIC-AMINES IN N,N-DIMETHYLFORMAMIDE - Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 1991)
The reduction of benzenesulfonyl derivatives of n-butylamine and N,N-di-n-butylamine with nitro substituents at the 2, 3 and 4 positions of the phenyl ring in N,N-dimethylformamide is reported. The N,N-di-n-butyl-4- and N-n-butyl-2-nitrobenzenesulfonamides are reduced in two cathodic steps. The first one, at about -0.90 V vs. SCE, a reversible one-electron process, gives a stable anion radical. The second reduction step at -1.70 V vs. SCE leads to cleavage of the S-N bond in good yields (> 70%). It is shown that the reduction of the N-n-butyl-3- and N-n-butyl-4-nitrobenzenesulfonamide is different, with three reduction steps. The first reduction step occurs with the formation of an unstable anion radical, which decomposes via N-H bond cleavage. The reduction of this sulfonamide anion occurs at -1.16 V vs. SCE and the third cathodic step arises at -1.70 V vs. SCE when the remaining radical anion is reduced to its dianion. The S-N bond cleavage is rapid but is always a minor process. The mechanisms of the reduction are discussed.